2021
DOI: 10.1038/s41598-021-95062-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher senescence associated secretory phenotype and lower defense mediator in urinary extracellular vesicles of elders with and without Parkinson disease

Abstract: Youth fountain and aging culprits are usually sought and identified in blood but not urine. Extracellular vesicles (EVs) possess parental cell properties, circulate in blood, CSF and urine, and provide paracrine and remote cell–cell communication messengers. This study investigated whether senescence‐associated secretory phenotype (SASP) and immune defense factors in EVs of urine could serve as biomarkers in elderly individuals with and without a comorbidity. Urine samples from young adults and elderly individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…One study used both CNS‐originating EVs and general EVs for ROC analysis, and we did not exclude it (Yan et al., 2022). Among the studies using general EVs, thirty of those studies did not include an ROC analysis (Athauda et al., 2019; Bhattacharyya et al., 2022; Cerri et al., 2018; Chan et al., 2023; Chan et al., 2021; Chan et al., 2023; Chung et al., 2020; Elkouris et al., 2019; Fraser et al., 2016; Han et al., 2019; Herman et al., 2023; Ho et al., 2014; Hong et al., 2023; Kitamura et al., 2018; Lamontagne‐Proulx et al., 2019; Leng et al., 2020; Leng et al., 2022; Miyamoto et al., 2023; Sproviero et al., 2021; Sproviero et al., 2022; Taymans et al., 2023; Wang et al., 2017; Wang et al., 2018; Wang et al., 2020; Wang et al., 2022; Xia et al., 2019; Yang et al., 2015; Yang et al., 2018; Yeh et al., 2021; Zhao et al., 2020), six did not include sensitivity or specificity (Grossi et al., 2021; Gualerzi et al., 2019; He et al., 2021; Ohmichi et al., 2019; Ruf et al., 2021; Yao et al., 2018), and one study only performed the ROC analysis directly in serum instead of EVs (Citterio et al., 2023). In total, the meta‐analysis included 21 studies (Barbagallo et al., 2020; Cao et al., 2019; Cao et al., 2020; Cao et al., 2017; Chung et al., 2021a; Chung et al., 2021b; Dos Santos et al., 2018; Gui et al., 2015; Hadisurya et al., 2023; Hong et al., 2021; Lucien et al., 2022; Manna et al., 2021; Shim et al., 2021; Stuendl et al., 2016; Stuendl et al.,…”
Section: Resultsmentioning
confidence: 99%
“…One study used both CNS‐originating EVs and general EVs for ROC analysis, and we did not exclude it (Yan et al., 2022). Among the studies using general EVs, thirty of those studies did not include an ROC analysis (Athauda et al., 2019; Bhattacharyya et al., 2022; Cerri et al., 2018; Chan et al., 2023; Chan et al., 2021; Chan et al., 2023; Chung et al., 2020; Elkouris et al., 2019; Fraser et al., 2016; Han et al., 2019; Herman et al., 2023; Ho et al., 2014; Hong et al., 2023; Kitamura et al., 2018; Lamontagne‐Proulx et al., 2019; Leng et al., 2020; Leng et al., 2022; Miyamoto et al., 2023; Sproviero et al., 2021; Sproviero et al., 2022; Taymans et al., 2023; Wang et al., 2017; Wang et al., 2018; Wang et al., 2020; Wang et al., 2022; Xia et al., 2019; Yang et al., 2015; Yang et al., 2018; Yeh et al., 2021; Zhao et al., 2020), six did not include sensitivity or specificity (Grossi et al., 2021; Gualerzi et al., 2019; He et al., 2021; Ohmichi et al., 2019; Ruf et al., 2021; Yao et al., 2018), and one study only performed the ROC analysis directly in serum instead of EVs (Citterio et al., 2023). In total, the meta‐analysis included 21 studies (Barbagallo et al., 2020; Cao et al., 2019; Cao et al., 2020; Cao et al., 2017; Chung et al., 2021a; Chung et al., 2021b; Dos Santos et al., 2018; Gui et al., 2015; Hadisurya et al., 2023; Hong et al., 2021; Lucien et al., 2022; Manna et al., 2021; Shim et al., 2021; Stuendl et al., 2016; Stuendl et al.,…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that SASP cytokines and immune defense factors could be identified in urinary EVs but not in urinary solutions. SASPassociated factors (e.g., IL-8, IP-10, GRO, and MCP-1) were detected at significantly higher levels in urinary EVs from old individuals (age >60) than young adults (Yeh et al, 2021).…”
Section: Cellular Alterations and Molecular Changesmentioning
confidence: 90%
“…CD63 was the surface protein of exosome, and CD63 was equivalent to an internal reference. It may be related to the age of PD patients [ 45 ]. This data indicated that we use the same amount of exosome to detect miR-184.…”
Section: Discussionmentioning
confidence: 99%